The Philosophy of Religion in Nishida Kitarō : 1901-1914 - Jacinto Zavala, Agustín (Théologiques)

(untitled) (Faculté de théologie et de sciences des religions, Université de Montréal, 2012)
The Study of Religion (Shūkyō-gaku) is an early text from a one-year course, 1913-1914, which Nishida Kitarō imparted only once in his academic career. In this text, apart from references to mystics and to early and medieval Christian thinkers, Nishida tries to point out the basic elements of Eastern and Western religions through the writings of xviii-xxth century authors, among them participants in the Gifford Lectures, the Bampton Lectures and Hibbert Lectures. On the other hand, Nishida tries to find the corresponding characteristics of religion in Zen and True Pure Land Buddhism. In short, Nishida’s approach to a philosophy of religion gives us an overview of the problems concerning a Buddhist-Christian dialogue.